2001
DOI: 10.1038/sj.onc.1204110
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity at 4p16.3 and mutation of FGFR3 in transitional cell carcinoma

Abstract: 4p16.3 has previously been identi®ed as a region of nonrandom LOH in transitional cell carcinoma, suggesting the presence of a tumour suppressor gene. One candidate within this region is ®broblast growth factor receptor 3 (FGFR3). Germline mutations in FGFR3 are known to cause several autosomal dominant skeletal dysplasias, the severity of which depends on the position and nature of the mutation in the protein. We investigated the frequency and nature of FGFR3 mutations in a panel of transitional cell carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 44 publications
5
67
0
Order By: Relevance
“…The identification of mutations in bladder cancers identical (K650/652Q) 18 or similar (K650/652T) (this study) to mutations found in hypochondroplasia suggests that other hypochondroplasia mutations, such as the I538/540V and N540/542K,T,S,V mutations in exon 13 may also occur in this carcinoma. 6,24 In other words, possible hypochondroplasia mutations in other exons than 15 may have escaped their detection in bladder cancer.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The identification of mutations in bladder cancers identical (K650/652Q) 18 or similar (K650/652T) (this study) to mutations found in hypochondroplasia suggests that other hypochondroplasia mutations, such as the I538/540V and N540/542K,T,S,V mutations in exon 13 may also occur in this carcinoma. 6,24 In other words, possible hypochondroplasia mutations in other exons than 15 may have escaped their detection in bladder cancer.…”
Section: Discussionmentioning
confidence: 94%
“…7,9 In the previous published series, only two FGFR3 mutations (A391/393E and K650/ 652Q) did not correspond to thanatophoric dysplasia mutations. 17,18 However, both mutations have been found to be associated with milder types of skeletal dysplasia: the A391/ 393E mutation with the Crouzon syndrome with acanthosis nigricans and the K650/652Q mutation with hypochondroplasia. In this new series of 297 bladder carcinomas reported here, we identified 181 FGFR3 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mutations are found in the immunoglobulin (Ig)-like loop domain, the transmembrane domain, and the tyrosine kinase domain, with the most common mutation on the Iglike loop domain: the S249C that occurs in up to 70% of tumors. 71 Because mutations of this gene are seen rarely in other solid tumors, with the exception of a small number of cervical carcinomas, it has been suggested that FGFR3 mutations are specific for UC and reportedly occur in Ͼ 40% of patients with UC. 72,73 Because it is believed that mutations of FGFR3 are very early events in bladder carcinogenesis, their detection in urine may be informative for diagnosing low-grade carcinomas with high sensitivity and specificity.…”
Section: Tumor Suppressors In Loci Of Losses and Deletionsmentioning
confidence: 99%